Effect of straws and irrigation methods in suppression of weeds - Guerra, Naiara; Oliveira Neto, Antonio Mendes de; Flora, Rodrigo; Guerra, Angélica; Meert, Leandro; Bottega, Eduardo Leonel (Revista de Ciências Agroveterinárias, 2015)
Two experiments were conducted in order to evaluate the influence of straws of different cultures subjected to two methods of irrigation in suppressing the development of weeds Ipomoea triloba and Euphorbia heterophylla. The tests were conducted on the campus of the Integrated College of Campo Mourão - PR during the months of September and October 2014. The treatments were arranged in a factorial design 2x6, the first factor was represented by two irrigation methods, which are superficial and subsurface and the second for five types of straw (sunflower, turnip, oats, beans and wheat) and a control without the presence of straw. Plant number evaluations were performed and number of leaves of I. triloba and E. heterophylla at 7, 14, 21, and 28 DAA, and in the last evaluation collecting area of the plant to obtain the dry weight was carried out. Overall, it was found that the turnip, oats, beans, and wheat, when they receive surface irrigation, promote smaller development of morning-glory plants and lower dry mass accumulation of poinsettia plants.